Аналіз експлуатаційних витрат легкового автомобіля - Агапов, Олег Миколайович; Пелипенко, Євген Сергійович (Національний технічний університет "Харківський політехнічний інститут", 2024)
У статті розглянуто загальний підхід до визначення вартості володіння автомобілем, що включає витрати на вступ до стану володіння, витрати на експлуатацію та витрати на вихід із стану володіння. Особливу увагу приділено реальним експлуатаційним витратам, які враховувалися на прикладі конкретного автомобіля за досить тривалий період. На основі їх аналізу було визначено статті витрат та ступінь впливу кожної з них. В експлуатаційних витратах найбільше значення мають статті, пов'язані з придбанням палива та зберіганням автомобіля, а в сукупній вартості володіння – втрата вартості автомобіля за період, що аналізується та експлуатаційні витрати.

The paper considers a general approach to determining the cost of car ownership, including the costs of entry into ownership, the costs of operation and the costs of exit from ownership. Particular attention is paid to real operating costs, which were taken into account on the example of a particular car over a fairly long period of time. On the basis of their analysis, the items of expenditure and the degree of influence of each of them were identified. In operating costs, the most important items are those related to the purchase of fuel and storage of the car, while in the total cost of ownership - the loss of value of the car for the period under consideration and operating costs. Based on the obtained data, specific indicators characterising the total cost of vehicle ownership were determined, which explain the growing tendency, especially in large cities, to reduce the number of personally owned cars due to economic inexpediency, and, as a consequence, the active development of alternative forms of transport service organisation.
Analysis of car operating costs
Keywords: автомобіль; аналіз; експлуатаційні витрати; транспортні витрати; технічне обслуговування; витрати палива; статистичні дані; car; analysis; operating costs; transport costs; maintenance; fuel consumption; statistical data